Enamel microarchitecture of a tribosphenic molar - Spoutil, Frantisek; Vlcek, Vojtĕch; Horácek, Ivan (Journal of morphology, 2010)
The tribosphenic molar is a dental apomorphy of mammals and the molar type from which all derived types originated. Its enamel coat is expected to be ancestral: a thin, evenly distributed layer of radial prismatic enamel. In the bat Myotis myotis, we reinvestigated the 3D architecture of the dental enamel using serial sectioning combined with scanning electron microscopy analyses, biometrics of enamel prisms and crystallites, and X-ray diffraction. We found distinct heterotopies in enamel thickness (thick enamel on the convex sides of the crests, thin on the concave ones), angularity of enamel prisms, and in distribution of particular enamel types (prismatic, interprismatic, aprismatic) and demonstrated structural relations of these heterotopies to the cusp and crest organization of the tribosphenic molar. X-ray diffraction demonstrated that the crystallites composing the enamel are actually the aggregates of much smaller primary crystallites. The differences among particular enamel types in degree of crystallite aggregation and the variation in structural microstrain of the primary crystallites (depending upon the duration and the mechanical context of mineralization) represent factors not fully understood as yet that may contribute to the complexity of enamel microarchitecture in a significant way.
Keywords: Molar; Microscopy, Electron, Scanning; Dental Enamel; X-Ray Diffraction; lidé; moláry; mikroskopie elektronová rastrovací; difrakce rentgenového záření; zubní sklovina; Humans